2006
DOI: 10.1259/dmfr/24536918
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the incidence of central nodal necrosis in cervical lymph node metastasis and the extent of differentiation in oral squamous cell carcinoma

Abstract: The results indicated that if a patient had SCC with low-grade differentiation, CNN in small lymph nodes would be difficult to detect on CT scan. Therefore, noting changes in lymph node density in the absence of CNN on CT scans is necessary in case the primary tumour is low-grade SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Of 62 metastatic lymph nodes, 39 (62.9%) had low-attenuation areas in the center of the node on CT images, which is within the range of previous reports (60.9%-81.5%). [1][2][3]14 In 168 benign lymph nodes, 24 (14.3%) had low-attenuation areas in the center of the node, which, while within the range of previous reports (0%-28.8%), 1-3,14 is a relatively high incidence. In contrast to the slice thickness of 4 or 5 mm used in previous studies, [1][2][3]14 the slice thickness in the present study was 3 mm.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Of 62 metastatic lymph nodes, 39 (62.9%) had low-attenuation areas in the center of the node on CT images, which is within the range of previous reports (60.9%-81.5%). [1][2][3]14 In 168 benign lymph nodes, 24 (14.3%) had low-attenuation areas in the center of the node, which, while within the range of previous reports (0%-28.8%), 1-3,14 is a relatively high incidence. In contrast to the slice thickness of 4 or 5 mm used in previous studies, [1][2][3]14 the slice thickness in the present study was 3 mm.…”
Section: Discussionmentioning
confidence: 55%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In many of these reports, the detection of low-attenuation areas in the center of the lymph node, identifi ed as central necrosis, was used as a criterion for the diagnosis of metastatic lymph nodes; these reports indicated that such low-attenuation areas indicate focal necrosis in tumor cell nests in the lymph nodes. 4,7,16 However, structures other than necrotic foci can also cause low attenuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have shown that, in cases of squamous cell carcinoma with low-grade differentiation, central nodal necrosis would be difficult to detect on CECT scans. 28 Other authors have stated that the size of lymph nodes did not significantly influence the detection capability. 29 Some authors have further stated that two major pitfalls in assessing for nodal metastasis by CECT and MRI include misinterpreting benign enlarged, reactive nodes and the inability to detect disease in normal-sized nodes that are not necrotic.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of metastasis is judged on the basis of the size and morphology of the visualized lymph nodes. With regard to the features within these lymph nodes, attempts have been made to check for the presence of central necrosis within the lymph nodes by enhanced computed tomography [20,21]. Massive type metastatic lymph nodes have more abundant stroma than non-massive type metastatic lymph nodes, and the contrast pattern revealed by this computed tomography scan may differ between the two types; however, there are few reports on the existence of such a difference.…”
Section: Discussionmentioning
confidence: 99%